ON INCLUSION BETWEEN \(ΛBV^{(p)}\), CHANTURYIA AND \(H_ω^{p}\) CLASSES - Ledari, Alireza Ahmadi; Naderi, Habib (Italian Journal of Pure and Applied Mathematics, 2015)
Dedicated to the memory of professor Parviz Azimi In this paper we prove inclusion relations between \(ΛBV^{(p)}\) and V[v] and give a necessary condition for the inclusion of \(ΛBV^{(p)}\) in classes \(H_ω^{p}\).